2011
DOI: 10.1016/j.ejcts.2011.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fontan conversion with arrhythmia surgery and pacemaker therapy☆

Abstract: Mid-term results of Fontan conversion with arrhythmia surgery and pacemaker therapy were acceptable. Restoration of regular rhythm might improve the postoperative NYHA status and the activity of the daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…In patients with atrial-pulmonary artery anastomosis and refractory arrhythmia, conversion to TCPC with surgical ablation (MAZE) and epicardial lead placement are recommended. Hiramatsu et al [25] demonstrated one-and five-year survival of 80% and 64%, respectively, after conversion. In the present study, the patients did not require reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with atrial-pulmonary artery anastomosis and refractory arrhythmia, conversion to TCPC with surgical ablation (MAZE) and epicardial lead placement are recommended. Hiramatsu et al [25] demonstrated one-and five-year survival of 80% and 64%, respectively, after conversion. In the present study, the patients did not require reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…[6,3335] Hiramatsu et al noted an improvement in New York Heart Association functional class after Fontan conversion with arrhythmia surgery and pacemaker therapy. [36] An analysis of Fontan 1 data showed that patients who had pacemaker placement had lower Physical Functioning Summary Scores, although this was not associated with change in score in the current analysis. [37]…”
Section: Discussionmentioning
confidence: 76%
“…Other centers have reported higher mortality rates of up to 10%. 54 A 2015 publication has questioned the traditional indications for the conversion procedure, citing a high (86%) 8-year transplant-free survival among patients undergoing "early conversion." 55 Early Fontan conversion improved NYHA class and reduced arrhythmia burden, although these findings need to be confirmed prospectively before this approach can be recommended as standard of care.…”
Section: Operative Interventions In Adult Congenital Heart Disease-rementioning
confidence: 98%